Birthweight ratio and outcome in preterm infants. Issue 1 (January 1990) - Morley, R; Brooke, O G; Cole, T J; Powell, R; Lucas, A
Abstract : The association between birthweight ratio and outcome was investigated in 429 infants born before 31 weeks' gestation. Birthweight ratio was calculated in each case as birth weight divided by mean birth weight for gestation (from reference data). It was shown that a given ratio corresponded to the same birth centile across the gestational age range studied; a ratio of 0.8 corresponding to the 10th centile. There was a linear relationship between birthweight ratio and requirement for mechanical ventilation and postneonatal mortality. Birthweight ratio was also strongly and linearly related to body weight, length, and head circumference at 18 months' corrected age. Overall, there was no association between this ratio and neurodevelopmental outcome to 18 months. However, the subgroup with the largest weights for gestation (birthweight ratio greater than or equal to 1.1), had significantly higher language subscores than all the other children. Our data show that conventional dichotomous categorisation of preterm infants into small or appropriate for gestation is inadequate when exploring the association between size for gestation and outcome.